Perbandingan Penerapan Even Driven Architecture (EDA) dan REST terhadap kualitas performa pa da pengembangan aplikasi IoT berbasis mobile - HARIS FIRMAN ARDIANSYAH (Fakultas Ilmu Komputer, 2026)
This research compares the operational performance of Representational State Transfer (REST) and Event-Driven Architecture (EDA) in a prototype-scale aquascape Internet of Things (IoT) application. Based on the ISO/IEC 25010 standard, the evaluation focuses specifically on Performance Efficiency and Reliability characteristics. Load testing was conducted using the k6 testing tool gradually up to an extreme load (500 RPS), while mobile application performance was evaluated using the Android Studio Profiler. The test results indicate that the EDA architecture is significantly superior. Under extreme pressure, REST experienced a severe bottleneck with throughput plunging to 37.90 req/s and CPU utilization dropping to 14.83% due to failures in processing the data queue. Conversely, EDA withstood the load with a stable throughput of 125.98 req/s. In terms of capacity, EDA proved to be 68% more capable, processing 181.59 transactions per second (tx/s) compared to REST. On the reliability aspect, both architectures achieved 100% availability under normal conditions. However, EDA's fault tolerance success rate (99.58%) far exceeded REST's (66.29%), proving that the asynchronous mechanism in EDA prevents cascading failures when a single component encounters an error. Furthermore, the evaluation on the user device showed that the EDA mobile application performed faster and was more efficient, utilizing only 25.1% of the CPU compared to REST which consumed 48%. In conclusion, EDA has proven to be a superior, more resilient, and highly efficient architecture choice for IoT ecosystems dealing with high-intensity data.
Keywords: Internet of Things; Aquascape; Microservices; REST; Event-Driver Architecture; ISO/IEC 25010